The State Personnel Policy Implementation and Professional Well-Being of Civil Servants in Siberia: Capabilities and First Results - Evgeny Aleksandrovich Boyko; Vera Nikolaevna Menshova (Управленческое консультирование)
The article is devoted to consideration of the state personnel policy as a key tool for the public service reforming and developing. It is shown that the reasons for the gap between intentions and real practice of the personnel policy implementation is internal caused by the influence of the human factor and connected with the meaning of the necessary transformations and personnel processes in the civil service area. Particular attention is paid to the issue of the integration the monitoring of professional civil servants well-being in the public administration in Russia. Based on the on-line survey results more than 9,000 civil servants of the RF subjects in Siberia the article treats this monitoring as a potential tool for identification of challenges, of risk factors and for seeking deeper objective reasons and improving areas.